Impact of HPV vaccination on anogenital warts and respiratory papillomatosis. Issue 6 (2nd June 2016) - Wangu, Zoon; Hsu, Katherine K.
ABSTRACT: Human papillomavirus (HPV), the most common sexually transmitted infection in the US and worldwide, can cause cancers, anogenital warts (AGW), and recurrent respiratory papillomatosis (RRP) in men, women, and children. Global incidence of AGW ranges from 160-289 cases per 100, 000 person-years and peaks in young men and women in the third decade of life. RRP has an estimated incidence of 3 per 1 million person-years in children. Pre-licensure trial efficacy, modeling and time-trend ecological studies have shown a significant short-term impact of 4vHPV vaccine. In girls aged 15-19 years, a previously published meta-analysis indicated that genital warts decreased significantly by 31%; stratified analysis revealed more substantial reductions in populations with high (≥50 %) vs. low (<50 % ) vaccination coverage (61% vs. 14%). Longer-term monitoring will reveal whether this impact continues under 9vHPV programs, and whether current declines in AGW are mirrored by declines in RRP.